2014
DOI: 10.14712/23362936.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Common Viper Bites in the Czech Republic - Epidemiological and Clinical Aspects during 15 Year Period (1999–2013)

Abstract: The aim of this study was to analyse most important epidemiological and clinical aspects of registered snakebites caused by a native common European viper Vipera berus in the Czech Republic over a period of 15 years (1999–2013). Data have been collected retrospectively from a database of the Toxinology Centre belonging to the General University Hospital in Prague. In total, 191 cases of snakebites caused by common viper were registered during the study period. Systemic envenoming occurred in 49 (25.7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…In Europe, the epidemiological studies of snakebites show that mortality is not a serious problem; nevertheless, most cases required hospitalization and a rapid recognition of symptoms because it is essential to decide if immunotherapy is required [3,4,6,12,13]. Usually, immunotherapy with antivenoms is indicated only to patients with systemic envenoming (approximately 4,000 annual cases in Europe), but it was suggested that antivenom should be indicated to young children and pregnant women—representing 50% of snakebite cases—even if they do not have systemic symptoms [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, the epidemiological studies of snakebites show that mortality is not a serious problem; nevertheless, most cases required hospitalization and a rapid recognition of symptoms because it is essential to decide if immunotherapy is required [3,4,6,12,13]. Usually, immunotherapy with antivenoms is indicated only to patients with systemic envenoming (approximately 4,000 annual cases in Europe), but it was suggested that antivenom should be indicated to young children and pregnant women—representing 50% of snakebite cases—even if they do not have systemic symptoms [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…For regions inhabited by several medically important snake species, the World Health Organization recommends the manufacture of polyspecific antivenoms that are effective against all possible regional snake varieties [2]. This is important because, as a rule, patients cannot identify the species that bit them; thus, an expert analysis of the shape of the snakebite is required [12]. In the present study, the safety and venom-neutralizing efficacy of Inoserp Europe—a new F(ab’) 2 polyvalent antivenom, designed to cover envenoming caused by medically important snakes of the Eurasian region—were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that Europe has a relatively high number of Vipera species with relevant medical aspects, and that Europe shows the most favourable habitat, the underestimation is even greater, confirming the fact that snakebite in Europe is a disease with neglected incidence, morbidity and mortality. This is also justified by the fact that sporadic individual case reports and case series are found in the literature 4–81 …”
Section: Introductionmentioning
confidence: 99%
“…The principal local effects of Vbb venom poisoning are haemorrhage, oedema, myonecrosis, bruising and pain [2,[6][7][8], and hypotension is the most important sign of systemic envenomation [8][9][10][11]. This is reflected in gastrointestinal problems, with recurrent vomiting, nausea, circulatory instability and haematological disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The most striking difference in pathological action on man is, however, in eliciting neurotoxic effects. These are very rarely observed in the case of Vbb venom bites but frequently in that of Vaa and constitute a medical emergency, since they can progress from ptosis to intense muscular weakness that can persist for several hours [4][5][6][7][8][9][10]. By analysing the Vbb venom proteome we proposed an explanation, at the molecular level, of the differences in clinical pictures inflicted by the Vbb and Vaa venoms.…”
Section: Introductionmentioning
confidence: 99%